Has the prevalence of overweight, obesity and central obesity levelled off in the United States? Trends, patterns, disparities, and future projections for the obesity epidemic. (4th February 2020) - Wang, Youfa; Beydoun, May A; Min, Jungwon; Xue, Hong; Kaminsky, Leonard A; Cheskin, Lawrence J
Abstract: Background: Obesity (OB) is a serious epidemic in the United States. Methods: We examined OB patterns and time trends across socio-economic and geographic parameters and projected the future situation. Large national databases were used. Overweight (OW), OB and severe obesity (SOB) were defined using body mass index cut-points/percentiles; central obesity (CO), waist circumference cut-point in adults and waist:height ratio cutoff in youth. Various meta-regression analysis models were fit for projection analyses. Results: OB prevalence had consistently risen since 1999 and considerable differences existed across groups and regions. Among adults, men's OB (33.7%) and OW (71.6%) levelled off in 2009–2012, resuming the increase to 38.0 and 74.7% in 2015–2016, respectively. Women showed an uninterrupted increase in OB/OW prevalence since 1999, reaching 41.5% (OB) and 68.9% (OW) in 2015–2016. SOB levelled off in 2013–2016 (men: 5.5–5.6%; women: 9.7–9.5%), after annual increases of 0.2% between 1999 and 2012. Non-Hispanic Blacks had the highest prevalence in women's OB/SOB and men's SOB. OB prevalence in boys rose continuously to 20.6% and SOB to 7.5% in 2015–2016, but not in girls. By 2030, most Americans will be OB/OW and nearly 50% of adults OB, whereas ∼33% of children aged 6–11 and ∼50% of adolescents aged 12–19 will be OB/OW. Since 1999, CO has risen steadily, and by 2030 is projected to reach 55.6% in men, 80.0% in women, 47.6% among girls and 38.9% among boys. Regional differences exist in adult OB prevalence (2011–2016) and across ethnicities; South (32.0%) and Midwest (31.4%) had the highest rates. Conclusions: US obesity prevalence has been rising, despite a temporary pause in 2009–2012. Wide disparities across groups and geographical regions persist. Effective, sustainable, culturally-tailored interventions are needed.